1927 Haw. Sess. Laws 209-217, AN ACT Regulating the Sale, Transfer and Possession of Certain Firearms and Ammunitions, and Amending Sections 2136, 2137, 2138, 2139, 2140, 2141, 2142, 2143, 2146 and 2147 of the Revised Laws of Hawaii 1925 (the "Small Arms Act"), §§ 23-24 - (:unkn) unknown (General Publisher, 1927)
Prohibited the transfer of a firearm to any person who does not present a permit authorizing the acquisition of a firearm. Violators subject to five hundred dollar fine, or up to one year imprisonment, or both.
--
Keywords: TRANSFER ONLY